Indonesian Islam - Timothy P. Daniels (International Institute of Islamic Thought, 2007)
Detailed, extensive, and provocative, this book presents and assesses twentieth- century Indonesian fatawa (legal rulings) on a range of issues. Over the course of his well-documented discussion of decisions rendered by four main Indonesian fatwa-issuing bodies, Hooker highlights their methods of reasoning and the authorities they heed. He argues “that only the fatawa can tell us what Islam is on” the continuum of merging state and religious authorities in Indonesia at the beginning of the twenty-first century (p. ix). Confronting the question of secularism and revelation, as well as tensions between new and old authorities, Hooker posits the authority of God, revealed Islamic knowledge, and 1,400 years of intellectual tradition intertwined with colonial and postcolonial state authority in complex ways. This book consists of an introduction, five chapters, and an epilogue and appendix of Indonesian fatawa sources. The substantial introduction begins by reviewing the ideas of several Middle Eastern reformers who had an influence on “defining” Indonesian Islam, especially in the early twentieth century. However, underscoring the distinctiveness of indigenous Indonesian Islam, Hooker describes its particular characteristics, such as its emphasis on the Shafi`i madhhab (legal school), local legal texts, sixteenthto eighteenth-century tasawwuf literature, royal court literature, and the diverse translation of Islamic prescriptions into daily life. Despite this diffuse localization of Islam, the Dutch colonial state and the subsequent Republic of Indonesia severely limited Islam’s public presence until the recent passage of two legal initiatives. Finally, Hooker discusses the “new scholasticism” in Indonesia, the crux of his introduction, in which he stresses four Indonesian intellectuals: Hazairin, Harun Nasution, Nurcholish Madjid, and Abdurrahman Wahid. He asserts that they represent a “creative” rather than a “responsive scholasticism,” first emerging in the 1960s, that is “self-confident enough to propose serious change, alteration,” and “adaptation of classic scholasticism” (p. 45). This section, which takes an optimistic tone toward these four intellectuals, appears to be disconnected from the rest of the book. None of them are closely related to the four fatwa-issuing bodies, except for Abdurrahman Wahid, a former leader of Nahdlatul Ulama (NU) and president of Indonesia who has become increasingly isolated from mainstream Indonesian Islam due to his perceived commitment to liberal democratic values over Revelation. On the other hand, a discussion of scholars prominent at significant historical junctures mentioned later in the text would have been more insightful and would have contributed to the author’s overall argument ...